x^{μ-1}(x^p-1)^{v-1}[1,∞]などの定積分

\begin{alignat}{2}
&(1)  \displaystyle\int_0^1 x^{μ-1}(1-x^p)^{v-1}dx=\frac{1}{p}B\left(\frac{μ}{p},v\right)  (μ \gt 0,\,v \gt 0,\,p \gt 0)\\
&(2)  \displaystyle\int_0^{\infty} x^{μ-1}(1+x^2)^{v-1}dx=\frac{1}{2}B\left(\frac{μ}{2},1-v-\frac{μ}{2}\right)  \left(μ \gt 0,\,v+\frac{1}{2}μ \lt 1\right)\\
&(3)  \displaystyle\int_1^{\infty} x^{μ-1}(x^p-1)^{v-1}dx=\frac{1}{p}B\left(1-v-\frac{μ}{p},v\right)  (v \gt 0,\,p \gt 0,\, p(1-v) \gt μ)
\end{alignat}









<証明>

\((1)\) \(x^p=t\) と置きます。\((px^{p-1}dx=dt)\)
\begin{alignat}{2}
\displaystyle\int_0^1 x^{μ-1}(1-x^p)^{v-1}dx&=\displaystyle\int_0^1 t^{\frac{μ-1}{p}}(1-t)^{v-1}\cdot \frac{1}{pt^{\frac{p-1}{p}}}dt\\
&=\frac{1}{p}\displaystyle\int_0^1 t^{\frac{μ}{p}-1}(1-t)^{v-1}dt=\frac{1}{p}B\left(\frac{μ}{p},v\right)
\end{alignat}以上より$$\displaystyle\int_0^1 x^{μ-1}(1-x^p)^{v-1}dx=\frac{1}{p}B\left(\frac{μ}{p},v\right)$$







\((2)\) \(1+x^2=t\) と置きます。\((2xdx=dt)\)
\begin{alignat}{2}
\displaystyle\int_0^{\infty} x^{μ-1}(1+x^2)^{v-1}dx&=\displaystyle\int_1^{\infty} (t-1)^{\frac{μ-1}{2}}t^{v-1} \cdot \frac{1}{2\sqrt{t-1}}dt\\
&=\frac{1}{2}\displaystyle\int_1^{\infty} (t-1)^{\frac{μ}{2}-1}t^{v-1}dt\\
\end{alignat}\(\displaystyle t=\frac{1}{s}\) と置きます。\(\displaystyle \left(dt=-\frac{1}{s^2}ds\right)\)
\begin{alignat}{2}
&=\frac{1}{2}\displaystyle\int_1^0 (1-s)^{\frac{μ}{2}-1}s^{1-v}\left(-\frac{1}{s^2}\right)ds\\
&=\frac{1}{2}\displaystyle\int_0^1 (1-s)^{\frac{μ}{2}-1}\cdot s^{1-\frac{μ}{2}} \cdot s^{-1-v}ds\\
&=\frac{1}{2}\displaystyle\int_0^1 s^{-v-\frac{μ}{2}}(1-s)^{\frac{μ}{2}-1}ds=\frac{1}{2}B\left(\frac{μ}{2},1-v-\frac{μ}{2}\right)
\end{alignat}以上より$$\displaystyle\int_0^{\infty} x^{μ-1}(1+x^2)^{v-1}dx=\frac{1}{2}B\left(\frac{μ}{2},1-v-\frac{μ}{2}\right)$$







\((3)\) \(x^p=t\) と置きます。\((px^{p-1}dx=dt)\)
\begin{alignat}{2}
\displaystyle\int_1^{\infty} x^{μ-1}(x^p-1)^{v-1}dx&=\displaystyle\int_1^{\infty} t^{\frac{μ-1}{p}}
(t-1)^{v-1}\cdot \frac{1}{pt^{\frac{p-1}{p}}}dt\\
&=\frac{1}{p}\displaystyle\int_1^{\infty} t^{\frac{μ}{p}-1}(t-1)^{v-1}dt\\
\end{alignat}\(\displaystyle t=\frac{1}{s}\) と置きます。\(\displaystyle \left(dt=-\frac{1}{s^2}ds\right)\)
\begin{alignat}{2}
&=\frac{1}{p}\displaystyle\int_1^0 s^{1-\frac{μ}{p}}\left(\frac{1}{s}-1\right)^{v-1}\left(-\frac{1}{s^2}\right)ds\\
&=\frac{1}{p}\displaystyle\int_0^1 s^{1-\frac{μ}{p}}(1-s)^{v-1} \cdot s^{1-v} \cdot s^{-2}ds\\
&=\frac{1}{p}\displaystyle\int_0^1 s^{-v-\frac{μ}{p}}(1-s)^{v-1}ds=\frac{1}{p}B\left(1-v-\frac{μ}{p},v\right)
\end{alignat}以上より$$\displaystyle\int_1^{\infty} x^{μ-1}(x^p-1)^{v-1}dx=\frac{1}{p}B\left(1-v-\frac{μ}{p},v\right)$$

コメントを残す

メールアドレスが公開されることはありません。 * が付いている欄は必須項目です